Essential English 7 : Worktext in Literature and Language - Gonzales, Carolina T.; Francisco, Nelda R.; Yu, Pilar R. (Sampaloc, Manila : Rex Book Store, Inc., 2017)
"Essential English is an integrated English Series for Grades 7 to 10." It is different from other series in two important ways. First, it is organized to help you tie together your study of the language arts- literature, writing, and language. The literary text chosen for its relevance to your life and experiences serves as the starting point for all your learning. You will find literary selections that have been favorites for many generations, as well as works by contemporary writers. Second, as you use this book, it will encourage you to think for yourself, give you plenty of opportunities to make your own decisions based on a critical analysis of a given situation. All the parts of this worktext fit closely together. The series is thematically organized into four quarters, focusing on 21st century themes and categorized into Connections, Changes, Choices, and Challenges.
Includes bibliographical references.
English text